Harold D. Clarke og Moshe M. Czudnowki (eds.), Political Elites in Anglo- American Democracies, Changes in Stable Regimes, Dekalb, Illinois: Northern Illinois Press, 1987, 340 s. - Redaktionen, - (Politica, 1987)
-